2018
DOI: 10.1016/j.nicl.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Widespread diffusion changes differentiate Parkinson's disease and progressive supranuclear palsy

Abstract: BackgroundParkinson's disease (PD) and progressive supranuclear palsy – Richardson's syndrome (PSP-RS) are often represented by similar clinical symptoms, which may challenge diagnostic accuracy. The objective of this study was to investigate and compare regional cerebral diffusion properties in PD and PSP-RS subjects and evaluate the use of these metrics for an automatic classification framework.Material and methodsDiffusion-tensor MRI datasets from 52 PD and 21 PSP-RS subjects were employed for this study. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…PSP patients with vertical supranuclear gaze palsy exhibited lower FA values in the midbrain vs. those with slowness of vertical saccades, highlighting the role of midbrain atrophy in vertical ocular dysfunction (146). PSP-RS patients also showed more severe and widespread diffusion abnormalities vs. PD, which reflects greater microstructural damage as consistent with greater overall brain atrophy often found in PSP-RS than in PD cases (147). Moreover, damage to the SCPs may be detected in both PSP-RS and PSP-parkinsonism subtypes (130,145).…”
Section: Diffusion-weighted and Diffusion Tensor Imaging In Pspmentioning
confidence: 75%
See 1 more Smart Citation
“…PSP patients with vertical supranuclear gaze palsy exhibited lower FA values in the midbrain vs. those with slowness of vertical saccades, highlighting the role of midbrain atrophy in vertical ocular dysfunction (146). PSP-RS patients also showed more severe and widespread diffusion abnormalities vs. PD, which reflects greater microstructural damage as consistent with greater overall brain atrophy often found in PSP-RS than in PD cases (147). Moreover, damage to the SCPs may be detected in both PSP-RS and PSP-parkinsonism subtypes (130,145).…”
Section: Diffusion-weighted and Diffusion Tensor Imaging In Pspmentioning
confidence: 75%
“…When the two subtypes were directly compared, PSP-RS patients showed decreased FA and increased D in the left SCP vs. PSP-parkinsonism patients (145). Computer-aided diagnosis of PSP and its subtypes may be possible using diffusion-weighted/DTI measures (145,147).…”
Section: Diffusion-weighted and Diffusion Tensor Imaging In Pspmentioning
confidence: 99%
“…The highest AUC for PD vs. PSP was in the LC (0.94). In the same vein, Talai et al (65) found AUCs of 0.95 and 0.97 based on DTI metrics in the midbrain for PD vs. PSP. DTI abnormalities in the midbrain of patients with PSP reflect microstructural changes that precede the macrostructural changes revealed by midbrain atrophy (65).…”
Section: Diffusion Weighted Imaging Diffusion Tensor Imaging (Dti)mentioning
confidence: 89%
“…Lower FA and higher MD values suggest increasing disruption of white matter tracts and water content, respectively. FA in substantia nigra was shown to be reduced in IPD compared with healthy control, while FA was reduced and MD was increased in pons, cerebellum, MCP and putamen in MSA when compared with IPD and healthy controls, and FA was reduced and MD was increased in frontal white matter, midbrain, basal ganglion and SCP in PSP when compared with IPD [7476]. DTI is an emerging research tool to differentiate IPD and other neurodegenerative parkinsonism.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%